2015
DOI: 10.17221/284/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium fertilizer on grain yield, Se uptake and distribution in common buckwheat (Fagopyrum esculentum Moench)

Abstract: Selenium (Se) is a significant trace element for human and livestock animals because of its physiological functions. Se in plants, especially in the crop plants, is treated as a critical dietary source. The effects of foliar spray together with soil application of Se on Se uptake, distribution in common buckwheat (Fagopyrum esculentum M.) plants were discussed in this study. The results showed that both foliar spray and soil application of Se increased Se uptake in common buckwheat significantly (P < 0.05). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…Se application significantly increased wheat grain yield at regreening-jointing, jointing-heading, and heading-blooming stages, however, yield was not significantly affected by Se application at blooming-filling stage (Chu et al 2013). A positive effect of 5 g Se/ha for foliar spray on grain yield of common buckwheat was reported (Jiang et al 2015). Selenium at low concentrations acts as a growth stimulant whereas at high concentrations, it reduces root elongation and biomass production of wheat plants (Guerrero et al 2014).…”
Section: Resultsmentioning
confidence: 95%
“…Se application significantly increased wheat grain yield at regreening-jointing, jointing-heading, and heading-blooming stages, however, yield was not significantly affected by Se application at blooming-filling stage (Chu et al 2013). A positive effect of 5 g Se/ha for foliar spray on grain yield of common buckwheat was reported (Jiang et al 2015). Selenium at low concentrations acts as a growth stimulant whereas at high concentrations, it reduces root elongation and biomass production of wheat plants (Guerrero et al 2014).…”
Section: Resultsmentioning
confidence: 95%
“…According to Jiang et al [2015], Se accumulation in common buckwheat was closely associated with the application rate of Se, similarly in case of Germ et al [2013] the increase in Se concentrations in the grain of the double fortified plants was 6-fold greater in comparison to the Se-only bio-fortified plants. According to Poblaciones et al [2013] the difference in concentration between selenite and selenate was more evident as the dose increases.…”
Section: Selenium Contentmentioning
confidence: 96%
“…It confirms that sepsis can cause significant liver damage. EPO is an endocrine hormone with anti-inflammatory, antioxidant, anti-apoptotic effects [11][12], and in order to further clarify EPO value for the treatment of acute liver injury induced by sepsis, serum liver damage molecule level change in EPO group was analyzed in the study, and the results showed that serum ALT and AST levels of EPO group were significantly lower than those of CLP group. It is confirms that the EPO has a protective effect on liver function injury caused by sepsis.…”
Section: Discussionmentioning
confidence: 99%